Exploration of the Concept of Ethnomathematics in the Macapat Songs: Guru Gatra, Guru Wilangan and Guru Lagu - Endah Asmarawati; Maghfiroh Yanuarti (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2026)
Mathematics learning is often perceived as abstract and disconnected from students' cultural experiences, limiting meaningful conceptual understanding. Ethnomathematics offers an alternative perspective by integrating local cultural knowledge into mathematics education, thereby bridging formal mathematical concepts with everyday cultural practices. This study aims to identify and analyze the mathematical structures embedded in Tembang Macapat through its three canonical components: Guru Gatra, Guru Wilangan, and Guru Lagu. A descriptive qualitative approach was employed, using eleven types of Tembang Macapat: Maskumambang, Mijil, Sinom, Kinanthi, Asmaradana, Gambuh, Dhandhanggula, Durma, Pangkur, Megatruh, and Pocung. Data were collected through document analysis, participant observation, and semi-structured interviews with Javanese cultural experts and Macapat practitioners. The data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, while data credibility was ensured through source and method triangulation. The findings reveal that the structural elements of Tembang Macapat systematically embody mathematical concepts, including discrete structures, finite sequences, numerical regularity, controlled variation, numerical symmetry, and periodic rhythmic patterns. These findings demonstrate that the canonical rules of Macapat represent an integrated ethnomathematical system rather than merely literary conventions. The study contributes to ethnomathematics by providing a comprehensive mathematical interpretation of Guru Gatra, Guru Wilangan, and Guru Lagu, and by highlighting the potential of Tembang Macapat as a culturally responsive resource for teaching mathematical concepts while promoting students' conceptual understanding, motivation to learn, and appreciation of Javanese cultural heritage.